2017
DOI: 10.1038/s41598-017-18102-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Interactions of A Host Defense Antimicrobial Peptide Thanatin in Lipopolysaccharide Micelles Reveal Mechanism of Bacterial Cell Agglutination

Abstract: Host defense cationic Antimicrobial Peptides (AMPs) can kill microorganisms including bacteria, viruses and fungi using various modes of action. The negatively charged bacterial membranes serve as a key target for many AMPs. Bacterial cell death by membrane permeabilization has been well perceived. A number of cationic AMPs kill bacteria by cell agglutination which is a distinctly different mode of action compared to membrane pore formation. However, mechanism of cell agglutinating AMPs is poorly understood. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(118 citation statements)
references
References 69 publications
4
113
0
1
Order By: Relevance
“…In this case, it is important to verify that the label does not affect the structure and activity of the peptide. Finally, other types of binding interactions (e.g., with lipid II or LPS) can be examined using methods such as NMR, isothermal titration calorimetry (ITC) (e.g., thanatin, Sinha et al, 2017) or surface plasmon resonance (SPR) (e.g., Cg-Defh1, Schmitt et al, 2010; Table 1).…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, it is important to verify that the label does not affect the structure and activity of the peptide. Finally, other types of binding interactions (e.g., with lipid II or LPS) can be examined using methods such as NMR, isothermal titration calorimetry (ITC) (e.g., thanatin, Sinha et al, 2017) or surface plasmon resonance (SPR) (e.g., Cg-Defh1, Schmitt et al, 2010; Table 1).…”
Section: Other Methodsmentioning
confidence: 99%
“…The pore forming mechanisms, which have been characterized extensively in many papers (e.g., reviewed in Kumar et al, 2018), are shown in more detail. (Cheng et al, 2011;Wenzel et al, 2015); Magainin (Matsuzaki et al, 1998); HNP-1 (de Leeuw et al, 2010); Cg-Defh1 (Schmitt et al, 2010); Thanatin (Sinha et al, 2017); Esculentin-1a (Luca et al, 2013); LL-37 (Zeth and Sancho-Vaello, 2017) DNA target MIC; MBC -bactericidal a /Gel electrophoresis Buforin II (Park et al, 1998;Kobayashi et al, 2000Kobayashi et al, , 2004Xie et al, 2011); Indolicidin (Hsu et al, 2005;Marchand et al, 2006;Hale and Hancock, 2007;Hilpert et al, 2010) RNA target MIC; MBC -generally bacteriostatic a /Gel electrophoresis Attacin (Carlsson et al, 1991) Protein target MIC; MBC -generally bacteriostatic a /Co-precipitation; fluorescence Other target MBIC; MBEC e.g., gene down-regulation/targeting Nal-P-113 ; human β-defensin 3 (Zhu et al, 2013) a Based on (Finberg et al, 2004).…”
Section: Motivation For Studying Hdp Mechanism Of Actionmentioning
confidence: 99%
“…The new parameter set has been further expanded to include four new chemotypes: rmlC, galU, LPS Re and Lipid-A ( Figure 1). 30,31 Furthermore, these new atomic parameters have been used to examine the effect of different cations on the stability of the LPS membranes, 32 the binding mechanism of antimicrobial peptides and proteins to LPS membranes, [33][34][35] the effect of chemical remodeling on the structural dynamics and electrostatic properties of OM, 30,31 and to validate coarsegrained parameter sets for LPS from P. aeruginosa. 36,37 Concurrently, extensions of the GROMOS force field have been developed for the penta-and hexa-acylated forms of Lipid-A, LPS Re and Lipid-A modified with 4-amino-4-deoxy-L-arabinose from P. aeruginosa 38,39 and for the Rd1 LPS from E. coli, 40 followed by an extension of the CHARMM force field for the smooth LPS from E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Podisus maculiventris Thanatin, a cationic 21‐residue AMP adopts an hairpin structure and interacts with anionic groups of phospholipids through the Arg side chains (Robert et al, ). Thanatin forms a dimeric structure in complex with the LPS micelle (Sinha, Zheng, Mu, Ng, & Bhattacharjya, ). Notably, Thanatin has three lysine (14.3%), three arginine (14.3%), two proline (9.5%), and two cysteine.…”
Section: Discussionmentioning
confidence: 99%